Peran Brand Trust sebagai Pemediasi Hubungan Antara Nutrition Label dengan Keputusan Pembelian Mie Instan Lemonilo (Kota Pontianak) - Natal, Natalia; Mursalin, Adi (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2024)
As more and more people consume instant noodles, companies are competing to create various new flavors of instant noodles to attract consumers to make purchasing decisions. One of these variants is Lemonilo instant noodles, where the Lemonilo instant noodle product is very good to consume for body health. Consumer purchasing decisions will have a big impact on the company if it can maximize brand trust and nutrition labels on purchasing decisions for Lemonilo instant noodles among people in the city of Pontianaka. The method used in this research is a quantitative method where the population is the city of Pontianak and has a sample of 100 respondents from the people of Pontianak city who consume Lemonilo instant noodles. What was determined using a non-probability sampling technique, namely purposive sampling, was analyzed using the Partial Least Square (PLS) technique with the help of WarpPLS software. The results of this research show that nutrition labels have a positive influence on brand trust and nutrition labels also have a positive influence on purchasing decisions. Apart from that, brand trust has a positive influence on purchasing decisions and nutrition labels also have a positive influence on purchasing decisions with brand trust as mediation.